Sex Differences in the Prevalence, Awareness, Treatment, and Control of Diabetes Mellitus Among Adults Aged 45 Years and Older in Rural Areas of Northern China: A Cross-Sectional, Population-Based Study - Li, Jingyan; Ni, Jingxian; Wu, Yanan; Zhang, Hongyan; Liu, Jie; Tu, Jun; Cui, Jingqiu; Ning, Xianjia; Wang, Jinghua (Frontiers in Endocrinology, 2019)
Aims: Diabetes mellitus (DM) has reached epidemic proportions among adults worldwide, with China having the world’s largest population of individuals with the disease. Although the consequences of low rates of awareness, treatment, and control of DM are understood, sex-related differencesin these rates remain unknown. We assessed sex-related differences in the prevalence, awareness, treatment, and control of DMin a low-income, rural population in China. Materials and Methods: Individuals ≥45years old without cardiovascular disease were recruited into this study. The prevalence, awareness, treatment, and control of DMin both men and women were assessed after accounting for age, educational level, body mass index, and blood pressure. Results: A total of 3725 participants (women, 58.8%) were included. A male preponderance in the prevalence of DM was found among individuals aged 45–54 years, whereas there was a female preponderance among patients aged 65–74years and among those who were illiterate. Among individuals with >6 years of formal education, overweight individuals, and normotensive individuals, there was greaterDM awareness among women than among men. There was also a higher DM treatment rate among overweight women than among overweight men. However, better disease control was observed among men than among women for individuals aged 55–64-years, those with 1–6 years of education, and those with stage II hypertension. Conclusions: These results suggest that DM awareness should be improved among men and that regular DM screening should be implemented for men, especially young men. In addition, disease education and management should be strengthened for elderly women, especially those with low levels of education. The further study is necessary to explore this situation among representative population in China for making appreciate policy against DM.